2023
DOI: 10.26434/chemrxiv-2023-s6mp3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hydrogen Generation by Hydrolysis of Magnesium Hydride in Organic Acids Solutions

Abstract: Hydrolysis of MgH2 has a high theoretical hydrogen yield (15.2%) and is very attractive for onsite hydrogen production. However, the low solubility of Mg(OH)2 causes sluggish kinetics and incomplete utilization of MgH2. In this paper, we solve this problem by using organic acids (acetic, citric and oxalic) and nanoscale graphene-like carbon. The organic acid solution significantly increases the yield and rate of H2 generation due to its acidic nature. The hydrogen yield approaches 100% with a fast hydrolysis r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…A recently published article [46] outlined the main factors which can be used to control the reaction of MgH 2 hydrolysis in acidic solutions, including the type of the acid, the rate of its supply to the hydrolysis reactor, as well as the pH of the solution. Similar results further elaborated in this article were presented by the authors earlier, in the conference paper [47]; further details can be found in the preprint [48].…”
Section: Introductionsupporting
confidence: 89%
“…A recently published article [46] outlined the main factors which can be used to control the reaction of MgH 2 hydrolysis in acidic solutions, including the type of the acid, the rate of its supply to the hydrolysis reactor, as well as the pH of the solution. Similar results further elaborated in this article were presented by the authors earlier, in the conference paper [47]; further details can be found in the preprint [48].…”
Section: Introductionsupporting
confidence: 89%